Analysing recent meteorological trends and computation of reference evapotranspiration and its effect on crop yields in semi-arid region of Haryana - SANDEEP , RAWAL; YOGESH , KUMAR; ARADHANA , BALI; ANIL , KUMAR; RAJ , SINGH (MAUSAM, 2020)
Yield data of major crops and corresponding meteorological trends for the last forty-five years (1972-2016) were analysed for arid region (Hisar) of Haryana. Reference evapotranspiration (ET0) for the region was calculated based on Penman-Monteith equation. Meteorological parameters were subjected to Man-Kendall (MK) test for testing the significance and Sen’s slope estimator for estimating the magnitude of trend. Similarly, variability index was employed for computing variability in seasonal and annual weather parameters. Yield data was also subjected to MK test to estimate the annual increasing/decreasing trend over the years. During the last 45 years wind speed, sunshine hours and reference evaporation declined at a rate of 5%, 3.3% and 2% year-1 respectively while minimum temperature increased at 1.8% year-1. Average rainfall deficit of 1122 mm over evapotranspiration (ET0) was observed although it registered a declining trend owing to decline in ET0. The increasing trend in yield was found to be more in kharif season crops as compared to the same during rabi season. Cotton lint yield increased at a maximum rate (17.5% year-1) followed by pearl millet (7.8% year-1), rice (3.1% year-1) and barely (2.7% year-1) while no significant trend was observed in wheat, gram and pigeon pea yield during the study period.